An applied soundscape approach for acoustic evaluation - compatibility with ISO 12913 - Bilen, Asli Ozcevik; Can, Zerhan Yuksel (ELSEVIER SCI LTD, 2021)
Soundscape treats the acoustical climate depending on the complex interaction among multiple sound sources, properties of the environment, and society. Research published on soundscape since 1970s, display a great variety of aims, area selections, evaluation criteria, and therefore, methodologies. The ISO 12913 series on soundscape was first published in 2014, and since then, it has been developed to harmonize definitions, to regulate methods for data collection and reporting requirements as well as data analysis with their interpretations. This paper presents a research that aims to build up an applied soundscape approach developed for the evaluation, conservation, and rehabilitation of acoustical comfort in urban areas. The conceptual frame of this study is based on a methodology derived from field studies aiming to relate objective and subjective assessments of the urban environment. Besides, binaural sound recordings using soundwalk method, surveys including questionnaires, and semantic evaluations by the pairs of adjectives were obtained from the area. It is confirmed that the binaural recordings represent the actual sound environment by statistical analysis between subjective data obtained from on-site and the laboratory via recordings. The subjective data (pairs of adjectives) are correlated with the objective ones (sound quality metrics calculated through the recordings). Thus, the approach enables the qualitative judgments from the quantitative data by utilizing the listed equations for pairs of adjectives that can be described by the sound quality metrics. It is also documented that satisfaction from the sound environment is directly related to satisfaction from soundmarks. The methodology suggested by the study will provide significant benefits in the time-consuming field studies on urban acoustical comfort by ensuring rapid and systematic progress in related processes, which are obtaining, collecting, organizing, and archiving data. Thus, the need for on-site studies will be minimized. Furthermore, it is believed that the outcomes of the study will contribute to ISO 12913-2 and 3. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Soundscape; Acoustic evaluation; Sound quality metrics; Soundmark; ISO 12913; URBAN SOUNDSCAPES; ENVIRONMENTS; PERCEPTION; QUALITY; FIELD; Acoustics